2017
DOI: 10.1111/cas.13201
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA TUG1 promotes migration and invasion by acting as a ceRNA of miR‐335‐5p in osteosarcoma cells

Abstract: Long non‐coding RNA (lncRNA) have been the focus of increasing attention due to the role they play in many diseases, including osteosarcoma. The function of taurine upregulated gene 1 (TUG1) and its mechanism in osteosarcoma remain unclear. In our research, we found that TUG1 was elevated and correlated with a poor prognosis in osteosarcoma patients. In addition, the following functional experiment showed that decreased TUG1 could remarkably inhibit osteosarcoma cell migration and invasion, indicating that TUG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 51 publications
(96 reference statements)
4
98
0
Order By: Relevance
“…reported that the novel long intergenic noncoding RNA upregulated in CRC (UCC) promoted CRC progression by sponging miR-143. TUG1 plays a role in the regulation of many cancer types by functioning as a ceRNA Wang et al [22,32,34,35,53]. Based on the results of our bioinformatics analysis, it was hypothesized that miR-142-3p could be negatively regulated by TUG1.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…reported that the novel long intergenic noncoding RNA upregulated in CRC (UCC) promoted CRC progression by sponging miR-143. TUG1 plays a role in the regulation of many cancer types by functioning as a ceRNA Wang et al [22,32,34,35,53]. Based on the results of our bioinformatics analysis, it was hypothesized that miR-142-3p could be negatively regulated by TUG1.…”
Section: Discussionmentioning
confidence: 79%
“…In a ceRNA model, lncRNA release or upregulate target mRNA of miRNAs by competitively binding with the same miRNAs Zhang et al [27][28][29][30][31]. TUG1 participates in the progression and development of multiple tumors by acting as a ceRNA Zhang et al [22,24,26,[32][33][34][35][36]. To determine whether TUG1 acts as a ceRNA in HCC, we applied bioinformatics analysis (http://starbase.sysu.edu.…”
Section: Tug1 Regulates Zeb1 By Competitively Binding With Mir-142-3pmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is reported that lncRNA PTENP1 functioned as a ceRNA to modulate PTEN levels by decoying miR-106b and miR-93 in gastric cancer [33]. Similarly, Wang et al found that lncRNA TUG1 promotes migration and invasion by acting as a ceRNA of miR-335-5p in osteosarcoma cells [34]. In addition, lncRNA TUG1 has been revealed to stimulate human …”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…LncRNA‐TCONS_00026907 is involved in cervical cancer progression through inhibiting miR‐143‐5p (Jin et al, ). LncRNA MALAT1 can promote metastasis and proliferation by acting as a ceRNA of miR‐144‐3p in osteosarcoma cells (Wang, Yang et al, ). LncRNA TUG1 can promote migration and invasion by sponging miR‐335‐5p in osteosarcoma cells (Wang, Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%